z=49-53/13.4

Simple and best practice solution for z=49-53/13.4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for z=49-53/13.4 equation:



z=49-53/13.4
We move all terms to the left:
z-(49-53/13.4)=0
We add all the numbers together, and all the variables
z-(-53/13.4+49)=0
We get rid of parentheses
z-49+53/13.4=0
We multiply all the terms by the denominator
z*13.4+53-49*13.4=0
We add all the numbers together, and all the variables
z*13.4-603.6=0
Wy multiply elements
13.4z-603.6=0
We move all terms containing z to the left, all other terms to the right
13.4z=603.6
z=603.6/13.4
z=45+0.60000000000002/13.4

See similar equations:

| -6(x-3)=2(2x+4)-5x | | 5e/12-8=44 | | f+12/4=5 | | -3x^2-36x+9=0 | | -4{x-4}=44 | | z=49-43/13.4 | | –50u2=2 | | 21}8n-5=139 | | -5/9y=10 | | 4x+4=198 | | z-12=3z-40 | | 17=4u+1 | | 10–2x=–6+6x | | 3(x-4)=12x+15 | | 7a-15=50 | | 11z+12=15z-16 | | 77x-1=76 | | (7x+21)+75=180 | | 10u-4=9u+5 | | 5i(-2-4i)=0 | | -15+a=4a-3 | | 2x+131=306 | | 4+7x=6x-17 | | 2x+5/5=3x+1/2-x-7/2 | | 4e+15=-12 | | 4+2x=-4(8+4x) | | 10x+34=12x+6 | | -2(x-2=14 | | 4x-5(2x)14=0 | | p+41=8p-14 | | 100x^2+25x=0 | | 4(2+3x)=4+3 |

Equations solver categories